2010
DOI: 10.1089/cap.2009.0113
|View full text |Cite
|
Sign up to set email alerts
|

Six Months of Treatment with Risperidone May Be Associated with Nonsignificant Abnormalities of Liver Function Tests in Children and Adolescents: A Longitudinal, Observational Study from Turkey

Abstract: These findings suggest that risperidone treatment in the long term commonly leads to liver function changes, although at therapeutic doses in children and adolescents it may rarely induce a serious hepatic toxicity. Concomitant use of antidepressants and methylphenidate and variations in age and pubertal status are limitations of present study. Further studies are needed to assess the importance and role of other variables over LFT abnormalities in youth population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…To the Editor, Atypical antipsychotics have increasingly been used for the management of various psychiatric disorders of childhood and this may have important health consequences, including tardive dyskinesia (TD) (1)(2)(3)(4). The symptoms of TD in pediatric patients may be more complex than in adults and this may be related to shorter and episodic treatment durations (3).…”
Section: Letter To the Editormentioning
confidence: 99%
“…To the Editor, Atypical antipsychotics have increasingly been used for the management of various psychiatric disorders of childhood and this may have important health consequences, including tardive dyskinesia (TD) (1)(2)(3)(4). The symptoms of TD in pediatric patients may be more complex than in adults and this may be related to shorter and episodic treatment durations (3).…”
Section: Letter To the Editormentioning
confidence: 99%
“…Antipsychotic administration is associated with druginduced liver injury (DILI) since most of antipsychotic drugs are metabolized in the liver before being excreted through the kidneys. [5][6][7][8] The transaminase enzymes, aspartate transaminase (AST) and alanine transaminase (ALT) can be used as a biomarker of liver cell damage (hepatocellular injury), caused by numerous underlying etiologies including DILI. 9,10 Increased levels of free radicals/ROS (Reactive Oxygen Species) eventually cause hepatocytes damage, characterized by increased levels of AST and ALT.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic complications such as weight gain, hyperlipidemia, and insulin resistance are known side effects of AAP [2][3][4], and studies have suggested that youngsters are at an increased risk of these side effects compared to older adults [5]. With the decreased incidence of typical psychotic use in children and adolescents it is reasonable to speculate that children on AAP may be at a greater risk of disorders associated with metabolic syndrome, including nonalcoholic fatty liver disease (NAFLD) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%